Experimental investigation into microstructure, metallurgy and mechanical properties of AISI 422 stainless steel weldments produced using fibre laser welding direct forming. (2nd July 2016) - Lin, C.-M.; Yen, S.-H.; Tran, L.; Wu, Y.-E.; Wu, H.-C.; Tsai, H.-L.
Abstract : In this study, the Taguchi design method was used to determine the optimal parameters for the fibre laser welding direct forming (FLWDF) of AISI 422 stainless steel (SS) weldments for use in the repair of the tenons in steam turbine blades. Experiments were then conducted to investigate the microstructural characteristics and mechanical properties of the weldments. Our results show that the fusion zone of the AISI 422 SS weldments possesses a grain structure of significantly higher refinement than does the original AISI 422 SS. Moreover, tempering at 700°C for 2 h was found to enhance the hardness as well as the impact toughness of the weldments. Finally, mock-up trials of tenon repair were performed using the optimal FLWDF parameters. Our results reveal that the repaired tenons are able to withstand a tensile load of 30 kN in as-welded condition and up to 55 kN following tempering at 700°C for 2 h.